Assessing stingless bee reproductive biology, quantitative genetics, and the consequences of long-term management to support breeding initiatives - Koffler, Sheina (2017)
Meliponiculture (or stingless beekeeping) is a powerful tool for sustainable economic development in the tropics. However, meliponiculture has many challenges as it lacks standardization in management and breeding practices. The aim of this thesis was to investigate stingless bee reproductive biology combined to management and breeding as background to meliponiculture improvement. In chapter 1, we performed a meta-analysis of heritability across the Hymenoptera in order to review current knowledge and discuss the challenges for bee breeding and conservation. In chapter 2, we assessed how sexual selection acts on male traits in the stingless bee Scaptotrigona aff. depilis and identified which traits may affect male fitness. In chapter 3, we estimated heritability and genetic correlations for the traits studied in the previous chapter, to understand how evolution shapes male traits and to identify important traits for breeding programs. Finally, in chapter 4 we investigated how the environment and long-term management influence colony productivity in Melipona subnitida (jandaíra), a commercially managed species in Northeastern Brazil. Our results revealed that morphological traits exhibit higher heritability estimates than fitness related traits, and in general, colony productivity traits showed potential for breeding. However, few studies are available for stingless bees yet. Male aggregations in S. aff depilis selected competitive males with higher quality sperm, indicating the importance of this mechanism in stingless bee mating biology. The studied male traits exhibited high heritability estimates, with exception of sperm length. Since aggregations selected males with shorter sperm, these results suggest selection for long-term sperm storage by queens and higher fertilization potential. The assessment of M. subnitida records revealed that honey production was affected by climate and management, and strategies to improve beekeeping practices were discussed. We believe this thesis provides important guidelines to establish successful stingless bee breeding programs